Pharmacological Evaluation of Central Nervous System Effects of Ethanol Leaf Extract of Olax Subscorpioidea in Experimental Animals - Adeoluwa, O. A.; Aderibigbe, A. O.; Agu, G. O. (Drug Research, 2016)
Background:Olax subscorpioidea Oliv. (Olacaceae) is a medicinal plant used in folk medicine in the management of pain, mental illness, and convulsion. We evaluated neurosedative and anticonvulsant properties of the ethanol leaf extract of O. subscorpioidea (ELEOS).Methods: Effects of ELEOS (3.125, 6.25, 12.5, 25 mg/kg) on novelty-induced behaviors were determined using open field test. Anxiolytic effect of ELEOS (3.125, 6.25, 12.5, 25 mg/kg) was assessed using hole-board and elevated-plus maze paradigms. The effect of O. subscorpioidea on pentobarbitone sleeping time was also investigated. Anticonvulsant property of ELEOS (12.5–50 mg/kg) was evaluated using pentylenetetrazole, picrotoxin and strychnine-induced convulsions assays. The extract was administered once intraperitoneally.Results: The LD50 of ELEOS was 300 mg/kg. ELEOS (3.125, 6.25, 12.5, 25 mg/kg) significantly reduced rearing (99.8±2.8, 76.2±2.9, 37.4±1.2, 5.8±0.8) and grooming (48.0±3.6, 33.8±2.9, 25.4±1.6, 7.6±0.8) as compared with controls (185.8±5.1; 63.8±4.3). Treatment with ELEOS (3.125, 6.25, 12.5, 25 mg/kg) significantly reduced head-dipping on hole-board (10.6±1.9, 8.8±1.2, 7.2±0.9, 6.0±1.1) as compared with control (27.8±1.5). However, there was no anxiolytic effect on EPM. ELEOS (12.5, 25, 50 mg/kg) significantly prolonged pentobarbitone-induced sleeping time (43.0±1.4, 51.0±1.2, 61.0±1.8) as compared with control (31.0±0.7). At 50 mg/kg, ELEOS significantly prolonged onset of seizure (2.72±2.07) and latency to death (9.20±1.24) as compared with controls (0.54±0.02; 2.00±0.44) in pentylenetetrazole-induced convulsions with no effect on picrotoxin and strychnine-induced convulsions.Conclusion: The ELEOS is sedative and has mild anticonvulsant activity and this study supports pharmacological basis for its use in the management of mental illness and convulsion.
Keywords: convulsion; neurobehavioral; pentylenetetrazole; pentobarbitone